2022
DOI: 10.3390/plants12010120
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Different Hop (Humulus lupulus) Genotypes

Abstract: The antimicrobial activity of hop extracts obtained from different hop genotypes were investigated against Staphylococcus aureus and Lactobacillus acidophilus. In this study the pure xanthohumol, purified β-acids rich fraction, as well as α-acids with β-acids rich fraction were used to test antimicrobial activity against Staphylococcus aureus and Lactobacillus acidophilus; whereby, the antimicrobial activity of different hop extracts against Lactobacillus acidophilus was studied for the first time. Microbial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Stumpf et al 36 reported the growth inhibitory concentrations of the tannins against Staphylococcus aureus and found that these values increase with increasing concentration in the growth medium. These findings are also supported by a study conducted by Kolenc et al 37 that antibacterial activity of plants extracts against S. aureus and L. acidophilus was also dose dependent. Similarly, when the activity of tannins and their extracts was evaluated against E. coli similar results were observed that by increasing the dose, growth inhibitory effects also increased.…”
Section: Discussionsupporting
confidence: 84%
“…Stumpf et al 36 reported the growth inhibitory concentrations of the tannins against Staphylococcus aureus and found that these values increase with increasing concentration in the growth medium. These findings are also supported by a study conducted by Kolenc et al 37 that antibacterial activity of plants extracts against S. aureus and L. acidophilus was also dose dependent. Similarly, when the activity of tannins and their extracts was evaluated against E. coli similar results were observed that by increasing the dose, growth inhibitory effects also increased.…”
Section: Discussionsupporting
confidence: 84%
“…Through the GC–MS analysis ( Table 5 ), the top content in Sb-L-A was adlupulone (28.88%). Adlupulone [ 51 ] and lupulone [ 52 ] are also abundant in hop extracts and may mainly act to fight infections by pathogens [ 53 ]. These compounds might be useful alone or in combination with other active ingredients in Sb-L-A for antibacterial function.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the concentration of lactic acid in sample D2 was lower, there were no signs of spoilage. This is explained by the antimicrobial properties of hop extract ( Kumar Verma et al, 2020;Kolenc et al, 2022). Due to the biostabilisation of the fermented milk beverage with yeast, the product was suitable for longer storage for 14 days at 6±2°C.…”
Section: Resultsmentioning
confidence: 99%